Reverberation negatively impacts musical sound quality for cochlear implant users. (September 2015) - Roy, Alexis T.; Vigeant, Michelle; Munjal, Tina; Carver, Courtney; Jiradejvong, Patpong; Limb, Charles J.
Abstract : Objective: Satisfactory musical sound quality remains a challenge for many cochlear implant (CI) users. In particular, questionnaires completed by CI users suggest that reverberation due to room acoustics can negatively impact their music listening experience. The objective of this study was to more specifically characterize of the effect of reverberation on musical sound quality in CI users, normal hearing (NH) non-musicians, and NH musicians using a previously designed assessment method, called Cochlear Implant-MUltiple Stimulus with Hidden Reference and Anchor (CI-MUSHRA). Methods: In this method, listeners were randomly presented with an anechoic musical segment and five-versions of this segment in which increasing amounts of reverberation were artificially added. Participants listened to the six reverberation versions and provided sound quality ratings between 0 (very poor) and 100 (excellent). Results: Results demonstrated that on average CI users and NH non-musicians preferred the sound quality of anechoic versions to more reverberant versions. In comparison, NH musicians could be delineated into those who preferred the sound quality of anechoic pieces and those who preferred pieces with some reverberation. Discussion/Conclusion: This is the first study, to our knowledge, to objectively compare the effects of reverberation on musical sound quality ratings in CI users. These results suggest that musical sound quality for CI users can be improved by non-reverberant listening conditions and musical stimuli in which reverberation is removed.